The effects of intrapartum synthetic oxytocin on maternal postpartum mood: findings from a prospective observational study - Takács, Lea; Seidlerová, Jitka Mlíková; Štěrbová, Zuzana; Čepický, Pavel; Havlíček, Jan (Archives of women's mental health, 2019)
Postpartum depression (PPD) affects up to 19% of all mothers, with detrimental effects on both mother and child. The antidepressant and anxiolytic effects of plasma oxytocin are well-documented, but it is still disputable whether synthetic oxytocin (synOT) may protect women against postpartum mood alterations. The current study examined the association between synOT intrapartum and maternal mood postpartum using a prospective design. Two hundred sixty women were screened for depressive symptoms in the last trimester of pregnancy and then again 6 weeks and 9 months postpartum using the Edinburgh Postnatal Depression Scale. They also completed Maternity Blues Questionnaire in the first postpartum week. The data concerning the intrapartum interventions and health status of the newborn were extracted from the medical records. Cox proportional hazards regression adjusted for a history of depression, mode of delivery, and childbirth experience showed that synOT predicted a significantly lower risk of PPD (HR = 0.65, 95% CI 0.45-0.95, p = 0.025). The risk factors for PPD included a history of depression (HR = 3.20, 95% CI 2.33-4.40, p < 0.001) and negative childbirth experience (HR = 1.39, 95% CI 1.01-1.90, p = 0.040). Logistic regression adjusted for the same covariates found no significant effect of synOT on maternity blues (OR = 0.64, 95% CI 0.31-1.32, p = 0.23). While synOT administered intrapartum does not affect maternal mood immediately, it may come to effect some weeks after childbirth to protect mothers from developing PPD symptoms.
Keywords: proporcionální rizikové modely; Pregnancy; Humans; Longitudinal Studies; Oxytocin; Proportional Hazards Models; oxytocin; poporodní období; Female; rizikové faktory; dospělí; Psychiatric Status Rating Scales; Maternity blues; lidé; poporodní deprese; Oxytocics; Adult; Depression, Postpartum; ženské pohlaví; longitudinální studie; psychiatrické posuzovací škály; Pregnancy and postpartum; vedení porodu; Delivery, Obstetric; uterotonika; těhotenství; Synthetic oxytocin; Depression; matky; prospektivní studie; Postpartum Period; Mothers; Risk Factors; Prospective Studies